(3GdefXhe hGdefKhQ aj eLGdS GdUOhQs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s ((3YjSi Hf EHQGgje Hf jYbhH GdLYjOi s)
(3ChdgG (B:s
(3CeG HYO, agPG Led ef GdeLGdS ChVMJ ajgG CUhdkG ef cdGe GdCFeI ePchQjf s
(3BNQgG (B:s
(3hCHhYdi deQJVi, hGeI aGWeI GdRgQGA HfJ Cgd GdCUWaG hebOe Cgd GdUOb hGdhaG s
(3HChdgG agQS ddeLGdSs
(3HgG fXGe GdJYbjHIs
(3QJHg Ydi SHYI hSHYjf eLdSkGs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs